Subdural Hematoma Complicating Ventriculoperitoneal Shunts: An Algerian Centers Experience - Assoumane, Ibrahim; Al-Zekri, M.; Khelifa, A.; Touati, N.; Lagha, N.; Sidi Said, A.; Morsli, A. (Indian Journal of Neurosurgery, 2020)
Introduction Subdural hematoma can occur as a complication of a ventriculoperitoneal shunt (VPS), and it should be considered in any patient who present a shunt dysfunction or who does not show the expected recovery after revision of a shunt. Computed tomography (CT) scan is a quick and easy way of detecting subdural hematoma.Materials and Methods We conduct a retrospective study of 17 patients. All of them are admitted for a subdural hematoma on a VPS. The diagnosis in 13 cases is made by CT scan; three cases by brain MRI.Results We operated 16 patients and the evacuation of the hematoma with revision of the shunt was performed; we used an adjustable shunt for three patients and endoscopic third ventriculostomy in one case. The operative outcomes were favorable in 12 patients; there were 4 recurrences, 2 of which required evacuation of the hematoma through a bone flap.Conclusion The subdural hematoma is a complication observed during the surgical treatment of the hydrocephalus and can be a serious issue. We suggest that a brain CT scan should be routinely performed in symptomatic patients with VPS.
Keywords: subdural hematoma; hydrocephalus; ventriculoperitoneal shunt